Advancing Equality How Constitutional Rights Can Make a Difference Worldwide - Moseneke, Dikgang (University of California Press, 2020)
In a world where basic human rights are under attack and discrimination is widespread, Advancing Equality reminds us of the critical role of constitutions in creating and protecting equal rights. Combining a comparative analysis of equal rights in the constitutions of all 193 United Nations member countries with inspiring stories of activism and powerful court cases from around the globe, the book traces the trends in constitution drafting over the past half century and examines how stronger protections against discrimination have transformed lives. Looking at equal rights across gender, race and ethnicity, religion, sexual orientation and gender identity, disability, social class, and migration status, the authors uncover which groups are increasingly guaranteed equal rights in constitutions, whether or not these rights on paper have been translated into practice, and which nations lag behind. Serving as a comprehensive call to action for anyone who cares about their country's future, Advancing Equality challenges us to remember how far we all still must go for equal rights for all.